Cyclooxygenase-2 expression in actinic keratosis - Adamska, Kinga; Pawlaczyk, Mariola; Bowszyc-Dmochowska, Monika; Gornowicz-Piotrowska, Justyna; Janicka-Jedyńska, Małgorzata; Fedorowicz, Tomasz; Żaba, Ryszard (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Introduction : Actinic keratosis (AK) is a common age-associated dermatosis typical for skin with photo-ageing features. Actinic keratosis lesions transform into invasive squamous cell carcinoma, if left untreated, but inductive factors remain unknown. A role of prostaglandins in the neoplastic process has been postulated. Aim : To evaluate the possible correlation between cyclooxygenase-2 (COX-2) antigen expression in the immunohistochemical reaction and the stage of AK using the keratinocytic intraepiddermal neoplasia (KIN) classification, age, sex and skin phenotype. Material and methods : Skin samples of AK were examined histopathologically using the KIN classification. Immunohistochemical analysis of COX-2 expression was conducted using a commercially available kit and Image Processing and Analysis in Java. The intensity was presented as the percentage of cells with a positive reaction. Results : Out of the 94 subjects with AK (aged 51–93 years; mean: 76.51 ±9.64), 58 were female and 36 male. Phenotype 2 was found in 50 and phenotype 3 in 44 patients. Mean values of positive immunohistochemical reaction for COX-2 were 2.16 ±6.56% for women and 1.96 ±6.59% for men (2.47 ±6.61%), with no statistically significant difference. Mean values of anti-COX-2 antibody reaction were 2.30 ±6.82% in the KIN1 group and 2.48 ±7.01% in the KIN2 group, while no expression was found in all cases with KIN3. No statistically significant differences were found between the percentage of COX-2 positive cells in KIN1/KIN2. Conclusions : No statistically significant correlations between the intensity of COX-2 reaction and AK stage were found. Cyclooxygenase-2 expression in AK is not affected by age, sex, or skin phenotype.